RELATIONSHIPS BETWEEN ISLAM AND CHRISTIANITY IN THE MODERN CENTURY (International Conference on Social and Islamic Studies, 2022)
These two religions have the same origins. They both originate from the Abrahamic religion. Therefore, they both originally worship the same God. Islam and Christianity are also two of the three largest Abrahamic religions. The third one is Judaism. But they were founded in different eras. Judaism is the oldest, founded in the 7th century BCE. Then Christianity, founded in the first century CE. And the youngest of these three is Islam, founded in the 7th century CE. Islam and Christianity are both monotheistic religions. Below we saw that they have the same God. And they maintained the belief in that same God. The only difference is that these two religions gave different names to their God. The Islamic-Christian meeting in the modern era, the West experienced a new civilization by starting to annex the Eastern regions which were predominantly Muslim. While the Muslims at that time were experiencing a period of disunity among the Muslims. Islamic areas began to be colonized in the form of colonialism and imperialism. Meanwhile, on the African peninsula, France's presence was in stark contrast through the visit of Napoleon Bonaparte to several Muslim countries such as Egypt. This context gives a pattern that Islam has experienced a decline in civilization and access to advanced technology, all the way to Indonesia.